Carrier-envelope phase dependence in atomic ionization by short-laser pulses - Arbo, Diego (2009)
In atomic ionization by few-cycle laser pulses doubly differential momentum distributions near-threshold exhibit a radial nodal structure that results from peaked partial-wave distributions near a particular angular momentum. We analyze the doubly differential momentum distribution for different carrier-envelope phases. We find that in the cases where the photoelectron reaches a minimum at threshold the angular momentum distribution is very sensitive to the CEP since small variations of the ponderomotive energy can lead to the opening or closing of a new channel.